Nonidentical relations of skew-symmetric forms: Generation of closed exterior forms. Discrete transitions. Connection between field-theory equations and nonidentical relations - Petrova, Ludmila (International Journal of Advanced Mathematical Sciences, 2016)
Nonidentical relations of skew-symmetric differential forms, which basis are non-integrable deforming manifolds follow from differential equations. From nonidentical relations closed exterior forms are obtained. The process of obtaining closed exterior forms describes the discrete transitions and the emergence of structures and observable formations such as waves, vertices, and turbulent pulsations. It is shown that the field theory equations (by Schroedinger, Maxwell, Einstein and others) turns to be nonidentical relations, obtained from the mathematical physics equations for material media such as the cosmologic systems, the systems of charged particles and others.Â Â